2009
DOI: 10.1080/02786820902984811
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Artifacts from Conductive Silicone Tubing

Abstract: We report evidence that carbon impregnated conductive silicone tubing used in aerosol sampling systems can introduce two types of experimental artifacts: (1) silicon tubing dynamically absorbs carbon dioxide gas, requiring greater than 5 minutes to reach equilibrium and (2) silicone tubing emits organic contaminants containing siloxane that are adsorbed onto particles traveling through it and onto downstream quartz fiber filters. The consequence can be substantial for engine exhaust measurements as both artifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 20 publications
1
52
1
Order By: Relevance
“…Later, Beyersdorf et al (2012) showed that the near-idle scaling broke down with engine power settings greater than about 30%. Specifically, Beyersdorf et al (2012) showed that emissions of alkanes do not scale with other Matches key mass spectrum features observed in silicon oils Timko et al (2009) hydrocarbons and decrease more slowly with increasing engine power-the same conditions which favor soot production. Moreover, a recent FTIR study of the black carbon soot surface indicated that presence of alkane components in the absorption spectra (Cain et al 2010).…”
Section: Comparison With Other Products Of Incomplete Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Beyersdorf et al (2012) showed that the near-idle scaling broke down with engine power settings greater than about 30%. Specifically, Beyersdorf et al (2012) showed that emissions of alkanes do not scale with other Matches key mass spectrum features observed in silicon oils Timko et al (2009) hydrocarbons and decrease more slowly with increasing engine power-the same conditions which favor soot production. Moreover, a recent FTIR study of the black carbon soot surface indicated that presence of alkane components in the absorption spectra (Cain et al 2010).…”
Section: Comparison With Other Products Of Incomplete Combustionmentioning
confidence: 99%
“…Specifically, the siloxane factor was dominated by only a handful of masses: 73, 147, and 207. Timko et al (2009) previously ascribed these masses to siloxane contaminants associated with the use of silicone tubing. Silicone tubing was used for sampling exhaust in the APEX-3 campaign, so the identification of a siloxane factor was expected in the APEX-3 data.…”
Section: Factor Mass Spectramentioning
confidence: 99%
“…For the smallest particles here and elsewhere, the observed fluctuations in absolute and relative extinction cross-sections (Figures 1 and 2) are much greater for small particles than for larger particles, and measured σ ext are consistently and appreciably larger than theoretical predictions. Not only can surfactants alter scattering properties, but so can condensed water (Miles et al 2010) and methyl siloxanes that can off-gas from the conductive silicone tubing (Timko et al 2009) used in this and other aerosol instruments. Given these reasons, it is recommended that the extinction-minus-scattering method utilizing CRDS and nephelometery is limited to particles with diameters ≥200 nm.…”
Section: Psl Particle Comparison: Crds Nephelometery Mie Theorymentioning
confidence: 99%
“…Common practices were used to postcorrect the air beam (AB) to account for natural drift in the instrument sensitivity (Allan et al 2003b). As recommended by Timko et al (2009Timko et al ( , 2014, we have also removed signal contributions related to the contamination artifacts that arise from the fragmentation of aerosolized polydimethylsiloxane (SiO(CH 3 ) 2 ), found in conductive silicone tubing.…”
Section: Hr-ams Operationmentioning
confidence: 99%